2021
DOI: 10.3390/f12121653
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response to Weed Control and Fertilisation in Mid-Rotation Plantations of Eucalyptus pellita in South Sumatra, Indonesia

Abstract: We report on a study of mid-rotation weed control and nutrient management in Eucalyptus pellita plantations in South Sumatra. The study was established at two contrasting sites (representing high and low productivity for the region) that had previously carried three rotations of Acacia mangium. A combination of weed control, nitrogen (N), and phosphorus (P) fertiliser were applied at 1 and 2 years after establishment. We found that the addition of up to 250 kg N ha−1 applied either at 1 year or 2 years after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Both trials presented a positive growth response to the herbicide treatment in terms of H, DHB, and VOL, as reported by other authors [13][14][15]18,29,31]. A possible explanation may be the increment in the leaf area index and the photosynthetic rate of trees with less competition from understory vegetation, as reported by other authors [18,32].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Both trials presented a positive growth response to the herbicide treatment in terms of H, DHB, and VOL, as reported by other authors [13][14][15]18,29,31]. A possible explanation may be the increment in the leaf area index and the photosynthetic rate of trees with less competition from understory vegetation, as reported by other authors [18,32].…”
Section: Discussionsupporting
confidence: 80%
“…A possible explanation may be the increment in the leaf area index and the photosynthetic rate of trees with less competition from understory vegetation, as reported by other authors [18,32]. The results from the experiment demonstrated that at both sites, the understory vegetation development and E. globulus growth responded to weed control differently, possibly due to climate conditions, the timing of weed control operations, and understory vegetation composition [13,17,30,31]. Differences between treatments were evident from the start of the trial in Soure, being only perceived in Torres Vedras at a later stage of the experiment.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations